A Decision to Purchase Ms Glow Skincare at the Village Community of Pekan Dolok Masihul, North Sumatra: Viewed from Product Development and Prices - Selvi Ardianti; Hardi Mulyono; Abd. Rasyid Syamsuri; Lukman Nasution (Garuda Prestasi Nusantara Consulting, 2022)
This study aims to analyze the effect of product development and price on purchasing decisions for Ms Glow Skincare in the Pekan Dolok Masihul Village Community, Serdang Bedagai Regency, North Sumatra Province. Explanatory research is the methodology employed. From January 2022 to March 2022, this study was conducted. In this study, questionnaires with a Likert scale, documentation studies, and observation methods were employed to collect data. 300 participants made up the study's population, and 75 were selected for the sample using the Slovin formula with an a value of 10%. Multiple linear regression using the SPSS program is the analytical tool employed. The results of the partial test demonstrate that product development significantly and favorably influences consumer purchasing behavior. Price has a positive and significant impact on purchasing decisions in part. Then, concurrently, product development and price have a positive and significant impact on consumers' purchase choices for Ms. Glow Skincare in the Serdang Bedagai Regency, North Sumatra Province's Pekan Dolok Masihul Village Community.